Child perpetrators of homicide, suicide, and unintentional firearm fatalities in the United States - Solnick, Sara J. (The Routledge international handbook of juvenile homicide, 2024)
Violent death caused by children under the age of 15, whether intentional or unintentional, has received little attention in the literature. In this chapter, we use data from the National Violent Death Reporting System to investigate three types of fatality: homicide with child suspects, unintentional firearm fatalities caused by children, and child suicide. Data include complete reporting from 32 states in 2017 and 37 states in 2018. Based on the populations of the states in our data, we estimate that each year in the United States, 82 children become homicide suspects, 624 children commit suicide, and 71 are the cause of an unintentional firearm death, either to themselves or someone else. The large majority of child killers and their victims are male. Over 90% of the victims are children and over 80% of the events occur at home. We divide the states into three levels of household gun ownership and find that children in low-gun states are much less likely to kill with a firearm and, overall, they are less likely to commit a homicide or suicide, or be the perpetrator in an unintentional firearm death.